Affective touch enhances low gamma activity during hand proprioceptive perception in children with different neurodevelopmental conditions - Sabater-Gárriz, Álvaro; Mingorance, José Antonio; Mestre-Sansó, Francesc; Canals, Vicent; Bleyenheuft, Yannick; Montoya, Pedro; Riquelme, Inmaculada (Frontiers in Human Neuroscience, 2025)
BackgroundGamma wave activity in the sensorimotor cortex is a critical neural mechanism associated with proprioceptive processing, which is essential for motor coordination, balance, and spatial orientation. The modulation of gamma oscillations by different types of tactile stimuli, including affective touch, is not well understood, particularly in children with neurodevelopmental disorders such as cerebral palsy and autism spectrum disorder.AimsThis study aims to explore how affective touch influences gamma oscillatory activity and proprioceptive performance in children with typical development, cerebral palsy and autism spectrum disorders.Methods and proceduresEEG data were recorded from participants during passive wrist mobilizations under three conditions: following an affective touch stimulus, after a non-affective touch stimulus, and with no tactile stimulation. Time-frequency analysis of low gamma activity (30–45 Hz) on the left somatosensory cortex was conducted for each condition. Proprioceptive performance was assessed through participants’ accuracy in identifying wrist positions. Proprioception and pleasantness of affective and non-affective touch were also assessed.ResultsAffective touch increased proprioceptive gamma power density. Children with cerebral palsy had poorer proprioception and higher brain gamma power density for processing movement than children with typical development or autism, and their proprioception worsened with non-affective touch.Conclusion and implicationsThese findings highlight the potential of affective touch to modulate gamma oscillatory activity and enhance proprioceptive function, particularly in children with cerebral palsy. The results underscore the importance of incorporating emotionally meaningful sensory inputs in therapeutic interventions to support proprioceptive and motor function in children with neurodevelopmental disorders.